Inequalities in Retirement Age and Life Expectancy - Levente Sándor NÁDASI; Zsuzsanna TRÓN (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2023)
In the countries of the world as well as in the European Union, the continuous growth in life expectancy at birth is accompanied by an increase in retirement age. Comparing these age limits to the expected lifespan for men and women, we find huge differences between the expected years spent alive after retirement. In this paper, we examine one aspect of sustainability of different European pension systems, concentrating mainly on life expectancy and retirement age. On a large sample, we analyse how the governments change the retirement age for men and women and how it relates to demographic factors such as ageing and fertility. Considering that the pension system is also a redistribution mechanism, sustainability can be seen as a trade-off between fairness and efficiency.